Measuring unmeasurable: How to map laws to numbers using leximetrics - Konstantin A. Kholodilin; Linus Pfeiffer (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
As the institutional literature convincingly shows, socioeconomic phenomena are to a large extent shaped by the formal institutions, that is, legal acts (laws and ordinances). However, the latter are formulated in a specific language that is difficult to understand, let alone to measure. However, since the early 1990s, a whole branch of economic analysis of governmental regulations has evolved. It is known as leximetrics, i.e., the measuring of laws. It covers a wide range of economic sectors, such as financial, labor, housing, and product markets, among others. The two most popular methods are codification and surveys. Under the first method, the legal texts are analyzed, relevant provisions extracted, and numeric values assigned depending on these provisions. Under the surveys method, local experts are asked to provide their assessment of currently valid legal provisions and sometimes also their enforcement. In both cases, the legal texts are mapped onto real-valued indices with the objective of gauging the intensity of governmental regulations. These indices can be and are successfully used to explain the economic phenomena. This study provides a comprehensive overview of the leximetric literature and demonstrates interdependences between different types of governmental regulations.
Keywords: C43; H24; K25; R38; 330; leximetrics; governmental regulations; economics